2006
DOI: 10.1080/10641960601013617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sex Hormones on Non-Esterified Fatty Acids, Intra-Abdominal Fat Accumulation, and Hypertension Induced by Sucrose Diet in Male Rats

Abstract: Sucrose-fed rats (1) had higher intra-abdominal fat mass and plasma non-esterified fatty acids and lower testosterone levels, (2) were hypertensive, and (3) had lower plasma NO metabolites than controls. The lack of testosterone by castration of sucrose-fed rats decreased high blood pressure and circulating non-esterified fatty acids and increased NO metabolites. The administration of testosterone to castrated sucrose-fed rats restored hypertension, fat accumulation, and high-circulating non-esterified fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…Some of the mechanisms responsible for this could be the absence of androgens, since they are required to induce hypertension in fructose-fed rats, a variant of the sucrose-fed rats (Song et al, 2004) as observed in our model, and high blood pressure reappears when MS castrated animals receive treatment with testosterone (El Hafidi et al, 2006).…”
Section: Hypertensionmentioning
confidence: 88%
See 3 more Smart Citations
“…Some of the mechanisms responsible for this could be the absence of androgens, since they are required to induce hypertension in fructose-fed rats, a variant of the sucrose-fed rats (Song et al, 2004) as observed in our model, and high blood pressure reappears when MS castrated animals receive treatment with testosterone (El Hafidi et al, 2006).…”
Section: Hypertensionmentioning
confidence: 88%
“…In our laboratory, recent work has shown that Int MS rats sustain an increase of free saturated fatty acids, such as palmitic, stearic and oleic, and that this increase is positively correlated with the reduction of serum NO 3 − and NO 2 − concentration (El Hafidi et al, 2006). We can speculate that the free fatty acids have a direct effect on endothelial nitric oxide synthase (eNOS) (Davda et al, 1995).…”
Section: Intra-abdominal Fatmentioning
confidence: 96%
See 2 more Smart Citations
“…Os maiores níveis de NEFA observados no período pré-puberdade podem ser explicados parcialmente pelos menores níveis de testosterona neste período, concordando com os resultados obtidos por Hafidi et al (2006), que observaram a ocorrência de obesidade e aumento nos níveis circulantes de NEFA em ratos com baixos níveis de testosterona, porém, não foi observada correlação entre estes parâmetros neste estudo (P = 0,27). Os maiores níveis de NEFA no período pré-puberdade também podem justificar os níveis mais altos de GGT neste mesmo período, em comparação à puberdade, pois o maior aporte de NEFA provavelmente acarretou uma maior atividade hepática (GONZALEZ et al, 2011).…”
Section: Discussionunclassified